Recombination events in Neurospora crassa may cross a translocation breakpoint by a template-switching mechanism. - Yeadon, P J (2001)
To assist investigation of the effect of sequence heterology on recombination in Neurospora crassa, we inserted the Herpes simplex thymidine kinase gene (TK) as an unselected marker on linkage group I, giving a gene order of Cen-his-3-TK-cog-lpl. We show here that in crosses heterozygous for TK, conversion of a his-3 allele on one homolog is accompanied by transfer of the heterologous sequence between cog and his-3 from the other homolog, indicating that recombination is initiated centromere-distal of TK. We have identified a 10-nucleotide motif in the cog region that, although unlikely to be sufficient for hotspot activity, is required for high-frequency recombination and, because conversion of silent sequence markers declines on either side, may be the recombination initiation site. Additionally, we have mapped conversion tracts in His(+) progeny of a translocation heterozygote, in which the translocation breakpoint separates cog from the 5' end of his-3. We present molecular evidence of recombination on both sides of the breakpoint. Because recombination is initiated close to cog and the event must therefore cross the translocation breakpoint, we suggest that template switching occurs in some recombination events, with repair synthesis alternating between use of the homolog and the initiating chromatid as template.